Dehydroicetexanes in sediments and crude oils: Possible markers for Cupressoideae. (March 2019) - Nytoft, Hans Peter; Kildahl-Andersen, Geir; Lindström, Sofie; Rise, Frode; Bechtel, Achim; Mitrović, Danica; Đoković, Nataša; Životić, Dragana; Stojanović, Ksenija A.
Highlights: Structure of two dehydroabietane isomers (dehydroicetexanes) determined using NMR. Dehydroicetexanes are often abundant in high latitude coal and oil. Dehydroicetexanes are more stable than dehydroabietane. The ratio between isomers (trans/cis) reaches 83:17 at the start of the oil-window. Functionalized precursors having the icetexane skeleton are abundant in Cupressoideae. Abstract: Two previously unidentified dehydroabietane isomers were isolated from Miocene Serbian lignite and Rhaetian (Late Triassic) coaly mudstones from South Sweden and characterized using NMR-spectroscopy as cis - and trans -dehydroicetexane. Both have a 9(10 → 20)- abeo -abietane or icetexane skeleton, consisting of a 6-7-6 tricyclic framework with seven carbons in ring B instead of the usual six in common diterpanes of the abietane-type. Dehydroicetexanes can be detected using GC-MS-MS in m / z 270 → 146 chromatograms without interference from dehydroabietane or other isomers. Dehydroicetexanes are often abundant in high latitude coals and mudstones ranging from Triassic to Miocene, and in high latitude oils (Canada and Greenland) sourced from terrigenous organic matter. The trans /( cis + trans) dehydroicetexane ratio is low in immature sediments, but usually around 0.83 in oils and mature sediments with vitrinite reflectance (%Rr ) above 0.5, suggesting an equilibrium from the start of the oil window. Dehydroicetexanes are more stable than dehydroabietane and some oils, rich in dehydroicetexanes, contain no dehydroabietane. Precursors could be plant diterpenoids having the icetexane structure, which have been known for more than 40 years and isolated from a variety of higher plant sources, including some angiosperms. Many of the relatively simple icetexanes were isolated for the first time from Chamaecyparis pisifera and related species where they seem to be particularly abundant, suggesting that dehydroicetexanes may be used as markers for the genus Chamaecyparis or for Cupressoideae in general.